An evaluation of the neurotoxicity of pesticides and alcohol using human neuroblastoma cells and human progenitor cortical neural stem cells - Wijesekara Mudiyanselage, Anusha Udayangani Kumari Manike Wijesekara (2021)
Health concerns have been raised that the developing brain may be particularly vulnerable to the toxic effects of organophosphate (OP) and carbamate pesticides and alcohol. Invariably, many of the adult population are co-exposed to both pesticides and alcohol over the course of a lifetime, and for some individuals, also exposed in an acute setting. Chlorpyrifos and Azamethiphos are commonly used OP pesticides and Aldicarb is a commonly used carbamate pesticide. Safety testing of these commonly encountered neurotoxicants is a challenge to the area of development neurotoxicity. Induction of reactive oxygen species (ROS) has been proposed as a mechanism of acute OP, carbamate and alcohol induced poisoning cases, but there is uncertainty related to the cytotoxic responses associated with oxidative stress induced by these neurotoxicants. Herein, SH-SY5Y neuroblastoma cells and human embryonic progenitor cortical neuronal stem cells (hNPC) were used for evaluating ROS-mediated oxidative stress and cellular damage including elevation of protein carbonylation.